(De)Lithiation Mechanism of Hierarchically Layered LiNi1/3Co1/3Mn1/3O2 Cathodes during High-Voltage Cycling. Issue 3 (1st January 2019) - Hua, Weibo; Schwarz, Björn; Knapp, Michael; Senyshyn, Anatoliy; Missiul, Alkesandr; Mu, Xiaoke; Wang, Suning; Kübel, Christian; Binder, Joachim R.; Indris, Sylvio; Ehrenberg, Helmut
Abstract : In view of the requirements for high-energy lithium ion batteries (LIBs), hierarchically layered LiNi1/3 Co1/3 Mn1/3 O2 (NCM111) cathode materials have been prepared using a hydroxide coprecipitation method and subsequent high-temperature solid-state reaction. The diffraction results show that the synthesized NCM111 has a well-defined layered hexagonal structure. The initial specific discharge capacity of a Li/NCM111 cell is 204.5 mAh g −1 at a current density of 28 mA g −1 between 2.7 and 4.8 V. However, the cell suffers from poor capacity retention over extended charge-discharge cycles. The structural evolution of NCM111 electrode during electrochemical cycling is carefully investigated by in situ high-resolution synchrotron radiation diffraction. It is found that the nanodomain formation of a layered hexagonal phase H3 and a cubic spinel phase after charging to voltages above 4.6 V is the main source for the structural collapse in c direction and the poor cycling performance. This process is accompanied by the removal of oxygen, the transition metal (TM) migration and the crack generation in the nanodomains of the primary particles. These results may help to better understand the structural degradation of layered cathodes in order to develop high energy density LIBs.